Gambaran Karakteristik Perilaku Seksual dan Faktor-Faktor Terkait Pada Remaja di Kecamatan Kota Tengah - Ngabito, Siti Maryam; Nurbaiti, Nurbaiti (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Forms of sexual behavior such as premarital sex are one of the causes of adolescents vulnerable to HIV/AIDS. HIV/AIDS cases in 2020 in Gorontalo Province in adolescents 15-24 years old amounted to 30%. The purpose of the study was to obtain an overview of the determinants of sexual behavior in adolescents in Gorontalo Central City District. Descriptive survey research with a population of 1,977 adolescents (15-18 years old) and a sample of 333 people using purposive sampling technique and univariate data analysis. The results showed that out of 333 respondents, 111 respondents (33.3%) had severe sexual behavior and 222 respondents (66.7%) had mild sexual behavior. The forms of sexual behavior that have been carried out by respondents are dating 62.8%, fantasizing sex 31.8%, holding hands 65.2%, kissing cheeks and foreheads 28.5%, hugging 31.5%, kissing lips 12.9%, fingering sensitive areas 10.5%, petting 4.2% and having sexual intercourse 2.1%. The results of the two-variable analysis showed that the majority of severe sexual behavior was found in adolescents with a lack of knowledge 60.0%, in adolescents with access to a lot of positive information media 38.1%, in adolescents who had high-risk leisure activities 92.9% and in adolescents who were exposed to pornography 52.0%. It is expected that adolescents fill their spare time for more useful things, and this research can be a reference for the Central City District government and parents in fostering adolescents.